Mechanical and acoustic characteristics of interbedded rock samples under cyclic loading-unloading conditions - Wei, Dong (Frontiers in Earth Science, 2025)
In view of the unknown mechanical response behavior of weak interlayer surrounding rock under complex stress environment, this paper adopts laboratory experimental research method to carry out uniaxial compression and cyclic loading and unloading tests on natural rock mass and water-saturated rock mass, and compares the strength, deformation, failure mode and acoustic emission characteristics of rock mass. The mechanical behavior and warning signal of weak interlayer rock mass under cyclic loading and unloading are studied. The results show that cyclic loading reduces the strength of natural rock mass, and water saturation further weakens the strength of rock mass. The strength attenuation rate of water-saturated rock mass is low, at 60.19%. The average deformation modulus of natural rock mass is 6.571 GPa, and the average deformation modulus of water-saturated rock mass is 3.646 GPa, indicating that water reduces the stiffness of rock mass. The failure modes include splitting shear under uniaxial compression and tensile shear damage under cyclic loading. Acoustic emission analysis found that during the unloading and reloading process, the rock mass has a short “step-like” silent period, and about 70% of the damage occurs in the last silent period before failure. This can be used as a prediction indicator of damage and provide a valuable reference for disaster warning in engineering applications.